D16(x−9y)2 Submit D=(2x+3y)3 Submit Factorise: 4x2−y2+6y−9. View Solution Free Ncert Solutions English Medium NCERT Solutions NCERT Solutions for Class 12 English Medium NCERT Solutions for Class 11 English Medium NCERT Solutions for Class 10 English Medium ...
Factorise8x3+27y3+36x2y+54xy2. View Solution Doubtnut is No.1 Study App and Learning App with Instant Video Solutions for NCERT Class 6, Class 7, Class 8, Class 9, Class 10, Class 11 and Class 12, IIT JEE prep, NEET preparation and CBSE, UP Board, Bihar Board, Rajasthan Board, ...
一II. Fill in the blanks Factorise: x^2+x+1/4=4 H5:Facotise:1/4x^2-x+1= 6 Factorise: 4x^2-4x+1=7 Factorise: x^2y^2-4xy+4=8 actorise:9-12t+4t^2=9 Factorise: ()^2+20xy+25y^2=().10 Factorise:+4mm+1=()2. 相关知识点: 试题来源: 解析 , (2/I+x)...
百度试题 结果1 题目Factorise:(i)x^3-2x^2-x+2 (ii) x^3-3x^2-9x-5( iij_x^3+13x^2+32x+20(iv)2y^3+y^2-2y-1 相关知识点: 试题来源: 解析 (i)LetPutting, we getis a factor of.So,(ii)LetPutting, we get 反馈 收藏
Answer to: Factorise the polynomial f(x) = 2x^3 +15x^2+3x-72 , if f(-3) = 0 . By signing up, you'll get thousands of step-by-step solutions to your...
【题目】C. Questions that require solutionsFactorise the following:(1) x^2-5x+6(2) 4x^2-5(3) 4x^2+8x-1 ;(4) 3t^2-4t-1 ;(5)2y2-4y+1;(6) 2x^2-10xy+9y^2(7) -x^2-xy+y^2 ;(8) 2x^2y^2+4xy-3(9) -y^2x-4x^2y+2x^3(10) (x^3+x)^2-2x(x+1)-3 ...
相关知识点: 试题来源: 解析 4 1/4n^2,m= m+1/2n(7a+6)(7a-6)⑥ (1/2y+1)^2(x+y+3)^28 (x+1)^4x(x-3)^2 210(x+1+y)(x+1-y) 反馈 收藏
58_expand-and-factorise Edexcel GCSE Mathematics (Linear) – 1MA0 ALGEBRA:EXPAND & FACTORISE Materials required for examination Items included with question papers Ruler graduated in centimetres and Nil millimetres, protractor, compasses,pen, HB pencil, eraser.Tracing paper may be used.Instructions...
8x+4x+22y–2y 12x–6y+26y 8x+6x–2x+22y–2yCompleteyourdiagram Lettersfornumbers:a+b=10,whatcouldaandbbe?ifa=2,b=8whatisa+b?ifa=25,b=5whatisa+b?Letters,numbersandarea 6 2 b 5 Area?2x6=12 Area?5xb=5b Letters,numbersandarea 4 a 4 a Area?4x4=16Area?axa=a2 Lettersandarea...
(i) x^2 + xy + 8x + 8y = x(x+y) + 8(x+y) = (x+y)(x+8) (ii) 15xy - 6x +5y - 2 = 5y(3x+1) -2(3x+1) = (5y-2)(3x+1) (iii) ax+bx-ay-by a(x-y) + b(x-y) (x-y)(a+b) (iv) 15pq + 15 + 9q + 25p = 5p(3q + 5) + 3(3q+5) =(5p+...